Analysing Tenth-Grade Students’ Difficulty and Their Perceptions in Writing Recount Text - Ilma Amalina; Henrikus Joko Yulianto (English Education Journal, 2024)
One of the most important skills in studying English, particularly for EFL students, is writing recount texts. However, a lot of students struggle to grasp the components needed to write the texts. With the focus on linguistic and structural components, this study investigates difficulties faced by tenth-grade students at SMA Al Fusha Kedungwuni when producing recount texts. Furthermore, it examined how students perceive these difficulties and how their perspectives correspond with the understanding of the writing process. A mixed-methods technique was used in the study, which combined an analysis of the students' recount texts with a survey of their perceptions. The text reveals that students face structural and linguistic difficulties in writing recount texts. Structural difficulties include unclear chronological order, inadequate orientation, unclear events, weak or missing reorientation, and difficulty managing length and detail. Linguistic difficulties include tense usage, vocabulary choice, cohesion, grammar, sentence structure, spelling, and punctuation. Students' perceptions show sufficient engagement with critical stages of the writing process, such as planning and revising. However, self-reported data may introduce bias, as students may not accurately assess their own difficulties. This highlights a gap between self-awareness and actual performance in writing recount texts. The findings suggest the need for teachers to emphasize their teaching on recount text structure, incorporating activities to strengthen understanding. In addition, students should master past tense grammatical rules and practice changingpresent tense to past tense. Curriculum developers should emphasize the writing process, provide detailed explanations, and integrate grammar instruction.